AN INVESTIGATION OF THE RELATIONSHIP OF EXTERNAL PUBLIC DEBT WITH BUDGET DEFICIT, CURRENT ACCOUNT DEFICIT, AND EXCHANGE RATE DEPRECIATION IN DEBT TRAP AND NON-DEBT TRAP COUNTRIES - Alam, Noor; Md. Taib, Fauzia (European Scientific Journal, ESJ, 2013)
One can treat budget deficit as the mother of public debt because appearance of the former usually leads to the creation of later. However, in case of external public debt ceteris paribus current account deficit and exchange rate depreciation also come into play and show their significant relationship with it. The literature shows mostly descriptive approach on the subject however this study designs a model wherein the relationship of external public debt with budget deficit, current account deficit, and exchange rate depreciation are empirically tested. The study is dichotomy that covers empirical analysis of panels of a group of six “Debt Trap Countries (DTC)” namely as, India, Indonesia, Nepal, Pakistan, Sri Lanka, and Thailand and eight “Non Debt Trap Countries (NDTC)” as Bangladesh, Fiji, Korea, Malaysia, Myanmar, Papua New Guinea, Philippines, and Singapore, of Asian Pacific Developing Countries (APDC). Findings showed a positive relationship of external public debt (EPD) with budget deficit (BD), current account deficit (CAD), and exchange rate depreciation (ERD). However, their strength of relationship varies in DTC and NDTC. A stronger coefficient of EPD, BD, and ERD indicated an explosive borrowing, a higher demand of external public debt, and heavy utilization of foreign exchange while a lower coefficient of CAD signaled for the diversion of borrowed funds towards adjustment in current account in case of DTC. Relatively a lower coefficient of EPD, BD, and ERD indicated less borrowing, less demand of debt, and less utilization of foreign exchange while a higher coefficient of CAD suggested that borrowed funds were not diverted towards adjustment in current account in NDTC. This signaled a prudent public debt management in NDTC as compared to DTC. An empirical attempt under the ecology of dichotomy is the main contribution of this study.